A Taxonomic Revision of Passiflora subgenus Astrophea (Passifloraceae sensu stricto) in Brazil - Mezzonato-Pires, Ana Carolina; Milward-De-Azevedo, Michaele Alvim; Mendonça, Cláudia Barbieri Ferreira; Gonçalves-Esteves, Vania (Phytotaxa, 2020)
Passiflora subgenus Astrophea is one of the five currently recognized subgenera of Passiflora. It is distributed throughout the neotropics, mainly in the Amazon rainforest. We present a taxonomic revision of species of Passiflora subgenus Astrophea occurring in Brazil, based on vegetative, floral and pollen morphology. A total of 31 species and 2 varieties were recognized and classified into four sections and two series. Four species were placed in section Capreolata, 2 species in section Leptopoda, 17 species and 2 varieties in section Pseudoastrophea and 8 species in section Botryastrophea, of which 4 were included in series Botryastrophea and 4 in series Carneae. Astrophea individuals can be identified by their variable habit, entire leaf-blades, two glands at the apex of the petiole or at the base of the leaf blade and white flowers with yellow corona and pink to purplish or red to orange hypanthium. We discuss the rediscovery of P. elliptica after 71 years and present new records of P. chlorina from Minas Gerais, additional information on the little-known P. phaeocaula, P. sclerophylla and P. mansoi var. glabra. Identification keys, complete descriptions, geographical distribution maps, etymology, taxonomic comments and illustrations are presented.